EKOTEOLOGI KRISTEN: TEOLOGI PENCIPTAAN DAN TANGGUNG JAWAB TERHADAP LINGKUNGAN - Riska Riska (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research, titled " Ekoteologi Kristen: Teologi Penciptaan dan Tanggung Jawab terhadap Lingkungan" aims to search the relationship between creation theology within the Christian context and the ecological responsibilities borne by Christians. Using a literature review method, this study analyzes various theological and environmental ethics literature to understand how Biblical teachings on creation shape Christian perspectives on environmental conservation. The primary focus of this research is on interpreting creation theology as a foundation for ecological commitment and environmental justice within Christian faith practice. The findings indicate that creation theology provides a robust theological basis for environmental responsibility, emphasizing humanity's role as stewards of the earth who must maintain the balance and harmony of God's creation. The study also identifies challenges faced by vulnerable communities due to environmental degradation and underscores the need for collective action and advocacy by the church and Christian communities to support fair and sustainable environmental policies. The conclusion highlights the importance of integrating theological principles with concrete actions in addressing contemporary ecological issues